What makes an effective Teacher Professionald Development video? - Chachage, Kristeen; Simmons, Hannah; Plaut, Daniel (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 16981242 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1136 ZenodoArchiveConcept: 16981241
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Rapid Evidence Review: Exploring existing coordination mechanisms or methods used by education researchers and or Ministries of Education in Africa to align EdTech research to national priorities that enable the use of evidence in foundational learning policy and implementation - Ampofo, Rudolph; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 17187867 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1139 ZenodoArchiveConcept: 17187866
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Rapid Evidence Review: Exploring existing coordination mechanisms or methods used by education researchers and or Ministries of Education in Africa to align EdTech research to national priorities that enable the use of evidence in foundational learning policy and implementation - Ampofo, Rudolph; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 17187872 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1140 ZenodoArchiveConcept: 17187871
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Rapid Evidence Review: Exploring existing coordination mechanisms or methods used by education researchers and or Ministries of Education in Africa to align EdTech research to national priorities that enable the use of evidence in foundational learning policy and implementation - Ampofo, Rudolph; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 17187878 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1141 ZenodoArchiveConcept: 17187877
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Rapid Evidence Review: Exploring existing coordination mechanisms or methods used by education researchers and or Ministries of Education in Africa to align EdTech research to national priorities that enable the use of evidence in foundational learning policy and implementation - Ampofo, Rudolph; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 17187882 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1142 ZenodoArchiveConcept: 17187881
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Strengthening School Oversight Through Remote Support: Successes and Shortcomings. - Frazer, Madleen Madina; Ampofo, Rudolph (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 16947951 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1135 ZenodoArchiveConcept: 16947950
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Climate, education, and AI: Challenges and opportunities - Haßler, Björn; Taruza, Takudzwa Charisse (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 17053743 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1138 ZenodoArchiveConcept: 17053742
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

How can AI-powered tools be used to support and assess foundational learning in low and middle income countries? - Aslan, Nawaz (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 16116150 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1132 ZenodoArchiveConcept: 16116149
Keywords: Hide; _r:AddedByMyEducationEvidence

How is AI upgrading, disrupting, and transforming the role of teachers in low and middle income countries? - Lester, Jennie (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 16114513 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1130 ZenodoArchiveConcept: 16114512
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

How is AI being used by education ministries to improve service delivery in low and middle income countries? - D'Rozario, Jonny (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 16114800 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1131 ZenodoArchiveConcept: 16114799
Keywords: Hide; _r:AddedByMyEducationEvidence

HDR - Haßler, Björn; Taruza, Takudzwa Charisse; Handigol, Apoorva (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15485110 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1119 ZenodoArchiveConcept: 15485109
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Technology-enabled interventions for psychosocial support and social and emotional learning in education in emergencies - Moustafa, Nariman; Mtungwa, Nothando (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15806037 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1128 ZenodoArchiveConcept: 15806036
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Exploring Teacher Digital Skills and Literacy Competencies: A curated list of frameworks and resources to inform UNICEF Thailand - Flam, Rebekka; Upadhyay, Arjun; Thang, Sarah (EdTech Hub, 2025)
This report was developed in response to a request from UNICEF Thailand for a curated list of digital skills and literacy frameworks designed for teachers. It reviews and compares 16 global, regional, and national frameworks to inform the development or adaptation of teacher-specific training and materials in Thailand. Key insights include the multidimensional nature of digital literacy, the central role of teacher development, and the alignment of learner-centred approaches with competency-based education (CBE). The report concludes with practical recommendations for policymakers, educators, and practitioners in Thailand involved in designing or implementing digital skills and literacy frameworks. Keywords: Digital literacy; digital skills frameworks; teacher competencies; Thailand; Southeast Asia; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15499486 ZenodoArchiveConcept: 15499485 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1120 2405685:I2DINV6N
Keywords: _r:AddedByMyEducationEvidence

Artificial Intelligence and Education Systems in 2035: Fourteen trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in artificial intelligence (AI) that might occur over the next 10 years. It begins by capturing fourteen trends, relating to AI that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15792725 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1125 ZenodoArchiveConcept: 15792724
Keywords: _r:AddedByMyEducationEvidence

Education in Conflict and Crisis in 2035: Twelve trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in the increase in global conflict and crises that might occur over the next 10 years. It begins by capturing twelve trends, relating to conflict and crisis, that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15792765 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1126 ZenodoArchiveConcept: 15792764
Keywords: _r:AddedByMyEducationEvidence

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15366685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1113 ZenodoArchiveConcept: 15366684
Keywords: _r:AddedByMyEducationEvidence

EdTech for Marginalised Learners in Southeast Asia: Perspectives from funders and providers on priorities, design, investment, and scaling considerations - Jayasinghe, Neema; Chrisani, Aprillia; Honda, Delanie; Gunawan, Clarissa Jazzlyne (EdTech Hub, 2025)
This report presents the findings of a landscape analysis of EdTech interventions designed for the Southeast Asian context. The analysis aims to understand the extent to which EdTech providers and funders in Southeast Asia address the needs of marginalised learners through their priorities in design, investment, and scaling decisions. It focuses on initiatives targeting marginalised groups and those with potential to scale. The research for the study included interviews with funders engaged in the Southeast Asian EdTech space to examine their perspective on EdTech’s impact on marginalised learners, the approaches they adopt to support inclusive solutions, and the drivers behind their investment decisions. This builds on EdTech Hub’s research for the ASEAN-UK SAGE programme, particularly on how EdTech could be used to support improvements in foundational literacy and numeracy, out-of-school children and youth, and learners with disabilities, as well as overcoming gender barriers to employment through the use of EdTech solutions. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15387632 ZenodoArchiveConcept: 15387631 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1117 2405685:SB7G3I83
Keywords: _r:AddedByMyEducationEvidence

Assessing the scale-up of a technology-supported, government-led teacher professional development programme in Tanzania: Considering issues of equity, agency, and adaptation, Round 2 Policy Brief - Chachage, Kristeen; Swai, Calvin; Hennessy, Sara; Adam, Taskeen; Koomar, Saalim; Hegwa Paskali, Jonathan; Massam, Winston; Mtenzi, Fredrick; Komba, Anneth; Jacob Mrpoe, Winfrida; Anthony, Gervace; Malibiche, Mustapha; et al. (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15388175 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1118 ZenodoArchiveConcept: 15388174
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Data-Driven Teacher Deployment in Sierra Leone: Practicalities and quantitative analysis of using a matching algorithm in the 2024/25 deployment cycle - Koutecký, Tomáš; Mackintosh, Alasdair; Huti, M; Adam, Taskeen; Godwin, Katie; Frazer, Madleen Madina (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15368231 ZenodoArchiveConcept: 15368230 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1115 2405685:ICRSXHTV 2405685:MUWUTSZS 2486141:MRAYINR3
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Parent and Caregiver Engagement in Kenya: Gaps, opportunities, and emerging questions for future research - Flam, Rebekka; Honda, Delanie; Ramesh Vasudevan, Sharanya; Mbugua, Wanjiku (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15352737 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1112 ZenodoArchiveConcept: 15352736
Keywords: _r:AddedByMyEducationEvidence

Transforming Teacher Deployment: Lessons from a matching algorithm tool - Frazer, Madleen Madina; Adam, Taskeen; Godwin, Katie; Mackintosh, Alisdair; Haßler, Björn (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15368169 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1114 ZenodoArchiveConcept: 15368168
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Shifting Power Dynamics in Education Decision-Making: Investigating the role of a matching algorithm to improve teacher deployment in Sierra Leone - Godwin, Katie; Cameron, Emma; Frazer, Madleen Madina; Dube, Gugulethu; Mackintosh, Alisdair; Koutecký, Tomáš; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15039164 ZenodoArchiveConcept: 15039163 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1103 2405685:IRFH43RX 2405685:SFNCI64Z 2486141:C9Q4ZDTR
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Rapid Evidence Review on Remote Teaching and Learning - Pacitto, Julia; Hayat, Amal; Hinks, Jessica; Emerusenge, Aime Parfait; Ullah, Noor; Rabi, Asma (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to teaching practices and pedagogies for emergency remote learning. The main aim of this review is to provide education decision-makers, funders, and implementers (among others) with a clear understanding of the available global evidence on effective practices in teaching when students are educated remotely during emergencies, and to assess the relevance of this evidence for low- and middle-income contexts. The findings of the RER are organised by the following five themes: (i) instructional design for remote learning in emergency contexts; (ii) student engagement and interactivity in emergency remote teaching; (iii) assessment, feedback, and pedagogical adaptation in remote teaching during emergencies; (iv) well-being, ‘Maslow before Bloom’, and pedagogies of care in emergency remote teaching; (v) teacher training and support in remote teaching during crises. It also identifies critical gaps in the literature on emergency remote teaching and learning, and suggest avenues for future productive research to address these gaps. Keywords: Education in Emergencies, remote learning, pedagogy, teaching methods, EdTech, emergency remote teaching An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14967648 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1098 ZenodoArchiveConcept: 14967647
Keywords: _r:AddedByMyEducationEvidence

AI in the Classroom: A rapid evaluation of AI-generated lesson plans in Islamabad’s public schools - Aslam, Nawaz; Qureshi, Ghada; Hassan, Syed Mustafa (EdTech Hub, 2025)
This report presents a rapid evaluation of AI-generated lesson plans currently being used in public schools in rural and urban Islamabad under the National Institute of Excellence in Teacher Education (NIETE). These centrally developed, scripted lesson plans are aligned with the national curriculum and built on the Gradual Release of Responsibility (GRR) model, with additional elements of the 5E and Inquiry-Based Learning (IBL) models in science, and the Concrete-Pictorial-Abstract (CPA) model in maths. Using a mixed-methods approach—including teacher surveys, focus group discussions, key informant interviews, and an expert rubric-based review—the study assesses the lesson plans' quality, relevance, and adaptability. Teachers expressed strong support for the lesson plans, especially in terms of reduced workload and structured delivery, though concerns were raised around flexibility, contextual responsiveness, and teacher agency. While the study does not evaluate student learning outcomes, it provides actionable insights and recommendations for improving the design, support, and implementation of AI-generated instructional tools, particularly as the programme scales to other provinces in Pakistan, such as Balochistan. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15077892 ZenodoArchiveConcept: 15077891 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1104 10.53832/edtechhub.1105 10.53832/edtechhub.1107 10.53832/edtechhub.1108 2405685:2PITNHGC 2405685:FR4GREKJ 2405685:XG7G3FDM 2405685:XKIEQVIQ
Keywords: _r:AddedByMyEducationEvidence

Usawa na maamuzi katika Mafunzo Endelevu ya Walimu Kazini yanayowezeshwa na Teknolojia nchini Tanzania: Zana za utafiti - Chachage, Kristeen; Swai, Calvin; Rwambali, Innocent; Hennessy, Sara; Koomar, Saalim; Massam, Winston; Jacob, Winnie; Anthony, Gervace; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Mwakabungu, Fika; et al. (EdTech Hub, 2025)
Kifurushi hiki kina zana za utafiti zilizotengenezwa na EdTech Hub, Chuo Kikuu cha Dodoma, Chuo Kikuu cha Aga Khan, na Taasisi ya Elimu Tanzania kwa ajili ya utafiti unaochunguza upanuzi na mabadiliko ya kuendana na mahitaji ya walimu na mazingira ya shule katika utekelezaji wa Mafunzo Endelevu ya Walimu Kazini (MEWAKA) unaojumuisha matumizi ya teknolojia. Katika kuandaa zana hizi, tumetumia zana zilizochapishwa katika awamu ya kwanza ya utafiti huu na mifano kutoka sehemu mbalimbali, kwa kuzingatia mifano mizuri ya utafiti kuhusu elimu. Tunaweka zana hizi zipatikane kwa watafiti wengine na watendaji tukitumai kuwa zitakuwa za manufaa. Zana hizi zinapatikana kwa umbizo linaloweza kuhaririwa ili wengine waweze kuhariri inavyofaa kwao. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14901456 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1097 ZenodoArchiveConcept: 14901455
Keywords: _r:AddedByMyEducationEvidence

Districts of Excellence Toolkit - Burgess, Flic; Beoku-Betts, Iman (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14832497 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1095 ZenodoArchiveConcept: 14832496
Keywords: Hide; _comingsoon; _r:AddedByMyEducationEvidence

AI Observatory Webinar Presentation: 7 headlines we have learned about unlocking learning outcomes in the age of AI - Luz, Gita (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15149320 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1110 ZenodoArchiveConcept: 15149319
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

AI Observatory Webinar Report: unlocking learning outcomes in the age of AI - Luz, Gita (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15149258 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1109 ZenodoArchiveConcept: 15149257
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Scaling Online Teacher Professional Development in Bangladesh: Bangladeshi teachers’ experiences of the online training for the National Curriculum Revision - Afzal, Nimra; Atuly, Afsana Sadiq; Mazari, Haani; Clark-Wilson, Alison (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15005589 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1102 ZenodoArchiveConcept: 15005588
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Strengthening the use of data for decisions on teacher deployment in Sierra Leone: A Geospatial Approach to Workforce Allocation - McBurnie, Chris; Frazer, Madleen Madina; Dube, Gugulethu; Godwin, Katie (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14608646 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1082 ZenodoArchiveConcept: 14608645
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Districts of Teaching Excellence Sierra Leone - Beoku-Betts, Iman; Burgess, Flic (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14794031 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1090 ZenodoArchiveConcept: 14794030
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Brief 1 - How DPL can support FLN and equitable learning in Kenya - Hinks, Jessica; Daltry, Rebecca (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14825837 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1091 ZenodoArchiveConcept: 14825836
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Brief 2 - Overview of the implementation of the tool and the support teachers require to implement DPL - Hinks, Jessica; Daltry, Rebecca (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14825850 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1092 ZenodoArchiveConcept: 14825849
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Brief 3 - Which design features enable successful DPL - Hinks, Jessica; Daltry, Rebecca (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14825860 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1093 ZenodoArchiveConcept: 14825859
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Brief 4 - How data from DPL tools can be utilised to support learning - Hinks, Jessica; Daltry, Rebecca (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14825872 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1094 ZenodoArchiveConcept: 14825871
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Exploring the Gender Differences in Technology Use for Educational Purposes at Home Among Students in Pakistan - Raza, Oneir; Hennessy, Sara (EdTech Hub, 2025)
This report examines gender disparities in the use of educational technology (EdTech) among students in Pakistan, with the aim of informing policies that foster more inclusive and equitable digital learning environments. Drawing on data from a survey of over 2,000 teachers and interviews with EdTech stakeholders in Islamabad, the report explores how sociocultural norms and parental attitudes shape differential access to and use of EdTech at home—particularly disadvantaging female students. It identifies key barriers including limited access to affordable internet and devices, low digital literacy among parents (especially mothers), and prevailing gender norms that restrict girls’ engagement with technology. The findings highlight an urgent need for targeted interventions that address both infrastructural and sociocultural challenges. Recommendations include: expanding subsidised internet and device access in underserved areas; launching community-based digital literacy programmes for parents; creating safe online spaces for female students; promoting positive gender representation in media; and organising inclusive EdTech initiatives to increase girls’ participation. By tackling these barriers through coordinated action, the report offers a roadmap to bridge the gender gap in EdTech adoption and enhance educational equity in Pakistan. Keywords: EdTech; gender; Pakistan; girls’ education; developing economies; educational technology An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14973585 ZenodoArchiveConcept: 14973584 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1057 10.53832/edtechhub.1099
Keywords: _r:AddedByMyEducationEvidence

Equity and Agency in Technology-Supported Teacher Professional Development in Tanzania: Research Instruments Pack - Chachage, Kristeen; Hennessy, Sara; Koomar, Saalim; Swai, Calvin; Massam, Winston; Jacob, Winnie; Anthony, Gervace; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Mwakabungu, Fika; Mrosso, Vicky; et al. (EdTech Hub, 2025)
This pack contains links to research instruments developed by EdTech Hub, the University of Dodoma, Aga Khan University, and Tanzania Institute of Education for the second phase of a study investigating the scale-up and local contextualisation of a national technology-supported teacher professional development programme known as MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, which translates as ‘teacher continuous professional development’ [TCPD] in English). The instruments draw on previously published research instruments used in Phase 1 of our research, plus examples from other sources that exemplify best practices in education research. We are making these tools available to other researchers and practitioners and hope that they will prove useful. They are provided in editable format so that others can modify them as they see fit. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14901418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1096 ZenodoArchiveConcept: 14901417
Keywords: _r:AddedByMyEducationEvidence

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694591 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1014 ZenodoArchiveConcept: 10694590
Keywords: _r:AddedByMyEducationEvidence

Cost-effectiveness of digital personalised learning: Three interventions from Kenya - Anonymised for Peer Review (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14260074 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1078 ZenodoArchiveConcept: 14260073
Keywords: _r:AddedByMyEducationEvidence

Teacher Deployment in Sierra Leone Using a Geographic Information System-Supported Preference Matching Algorithm: A systems analysis - Anonymised for Peer Review (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15368298 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1116 ZenodoArchiveConcept: 15368297
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Teacher Motivation: Exploring non-financial incentives in school-based teacher professional development in Tanzania - Anonymised for Peer Review (EdTech Hub, 2025)
High-income countries often use external incentives such as remuneration, professional pathways or accreditation to motivate teachers to engage in professional development. This paper reflects on the challenges of engaging teachers in school-based professional development in resource-scarce education environments where the use of such incentives is not feasible and explores practical strategies to motivate their engagement. In such contexts, where qualified teacher status and promotion are not tied to engagement in professional development, other means for encouraging teachers to take up professional learning opportunities are paramount. In this two-year, iterative, design-based implementation research study of a national teacher professional development initiative in Tanzania, non-financial incentives were tested in eight rural schools. Findings show that completion certificates motivated teachers; achievement certificates had mixed results due to doubt around the fairness of the peer-review process. Additionally, teachers were intrinsically motivated by other changes in the programme such as access to relevant digital modules which allowed for teacher agency, and by increased collegial relationships and collaboration. Keywords: teacher motivation; school-based teacher professional development; design-based implementation research; Tanzania, non-financial incentives; intrinsic and extrinsic motivation An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14648336 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1087 ZenodoArchiveConcept: 14648335
Keywords: Hide; _r:AddedByMyEducationEvidence

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14622107 ZenodoArchiveConcept: 14622106 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1085 2405685:KIEIX7NP
Keywords: _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

Resilient by Design: Ukraine’s EdTech Emergency Response. A qualitative study - Bhatt, Margi; Radford, Kate (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15656819 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1122 ZenodoArchiveConcept: 15656818
Keywords: _r:AddedByMyEducationEvidence

EdTech Policy Rapid Scan for Sub-Saharan Africa - Flam, Rebekka; Oyedele, Oluwatomisin (EdTech Hub, 2025)
This rapid scan presents a curated list of EdTech policies in sub-Saharan Africa, compiled in response to a request from the World Bank. Based on desk research from mid-2024, it highlights that most policies predate COVID-19, with few new ones emerging post-2020. Many countries lack dedicated EdTech policies, instead relying on broader ICT or education strategies. Common themes include digital infrastructure, distance learning, and teacher training, while gaps remain in support for marginalised learners. The report provides an overview of existing policies, while the highlighted trends offer insights for future policy development. Keywords: EdTech policy; education policy; sub-Saharan Africa; EdTech governance; digital learning; digital infrastructure An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14749795 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1089 ZenodoArchiveConcept: 14749794
Keywords: _r:AddedByMyEducationEvidence

Leveraging Existing Technology in Low-Resource Settings to Support Learning: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
This document serves as a practical guide for implementers and decision-makers on how available technologies can effectively support teaching and learning in schools worldwide. Drawing on existing evidence of successful EdTech interventions in low-resource settings, particularly within Southeast Asia, it offers guidance on the essential steps in the early phases of EdTech implementation. The report also provides recommendations for transitioning from the initial conception phase to developing a comprehensive implementation plan. Keywords: EdTech implementation guide; low-resource settings; ASEAN; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14727493 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1088 ZenodoArchiveConcept: 14727492
Keywords: _r:AddedByMyEducationEvidence

Using EdTech in Response to Climate Emergencies in Pakistan - Hayat, Amal; Mazari, Haani; Aslam, Nawaz (EdTech Hub, 2025)
This policy brief explores how EdTech can support a climate-resilient education system, drawing on insights from stakeholder consultations and EdTech Hub's research on learning continuity in response to climate emergencies following the 2022 Pakistan floods. While recovery efforts often focus on restoring physical infrastructure, we argue that a shift to long-term resilience against climate emergencies can be supported by strategic and contextually relevant use of EdTech. The brief highlights the importance of addressing the evolving needs of learners and teachers across all phases of emergencies through preparedness measures and cross-sectoral collaboration. Keywords: Pakistan floods; climate resilience; EdTech; Education in emergencies; South Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15851578 ZenodoArchiveConcept: 15851577 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7782171 10.53832/edtechhub.0160 10.53832/edtechhub.1129 2405685:333BJPIR
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Teachers and Technology in Rural Malaysian Classrooms: Insights from the T4 Teachers and Technology Global Survey - James, Cynthia; Hennessy, Sara (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 16760930 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1134 ZenodoArchiveConcept: 16760929
Keywords: _r:AddedByMyEducationEvidence

Rapport de l’échange de connaissances - Koomar, Saalim; Rasolohery, Hasiniavo; Oojorah, Avinash; Udhin, Waaiza (EdTech Hub, 2025)
This is a report on a knowledge exchange visit between the Ministry of National Education of Madagascar and the Mauritius Institute for Education. The visit focused on sharing lessons and discussing ongoing projects related to technology in education. Key objectives included presenting successes and challenges of distance learning, discussing pedagogical design and digital platforms, and exploring long-term collaboration. School visits provided insights into technology integration in classrooms and teacher experiences. The report details the workshop's activities, participants, and key points, emphasising the importance of data-driven projects, feedback mechanisms, and continuous evaluation. Recommendations for future collaboration include short-term actions like remote communication and training, medium-term initiatives like co-presenting at conferences and personnel exchange, and long-term goals like co-applying for regional research projects. Keywords: teacher professional development; Madagascar; Moodle; knowledge exchange; EdTech; pedagogy Ce rapport porte sur une visite d’échange de connaissances entre le Ministère de l’Éducation Nationale de Madagascar et le Mauritius Institute for Education. La visite avait pour objectif de partager les enseignements tirés et de discuter des projets en cours liés aux technologies éducatives. Les principaux objectifs comprenaient la présentation des succès et des défis de l’apprentissage à distance, la discussion sur la conception pédagogique et les plateformes numériques, ainsi que l’exploration d’une collaboration à long terme. Les visites d’écoles ont permis d’observer l’intégration des technologies en classe et l’expérience des enseignants. Le rapport détaille les activités de l’atelier, les participants et les points clés, en mettant l’accent sur l’importance des projets basés sur les données, des mécanismes de retour d’information et de l’évaluation continue. Les recommandations pour une future collaboration incluent : Actions à court terme : communication et formation à distance; Initiatives à moyen terme : co-présentation lors de conférences et échanges de personnel; Objectifs à long terme : candidature conjointe à des projets de recherche régionaux. Mots clés: formation pédagogique; Madagascar; Moodle; échange de connaissances; technologie dans l’éducation; pédagogie An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230830 ZenodoArchiveConcept: 14230829 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1061 10.53832/edtechhub.1075
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Harnessing EdTech for Neurodivergent Learners in LMICs: A Rapid Evidence Synthesis - Layachi, Aida; Plaut, Daniel (EdTech Hub, 2025)
As neurodivergent learners continue to face multifaceted challenges that affect their education, education systems, environments, and practices have struggled to address their needs adequately. This rapid evidence synthesis explores the current state of evidence regarding the use of educational technologies (EdTech) for neurodivergent learners in low-and middle-income countries (LMICs). The review was conducted in two phases to offer complementary insights on the topic. The first phase presents the findings regarding the use of EdTech for neurodivergent learners in LMICs. The second phase expands the focus, offering evidence and examples that extend beyond LMICs, providing a global perspective on how EdTech could be applied and adapted to LMICs to address different challenges faced by neurodivergent learners. The holistic framework for EdTech for neurodivergence presented in this synthesis provides insights and recommendations regarding the potential of EdTech in optimising systems, environments, and education practices. Keywords: EdTech, Neurodivergence, LMICs, holistic framework, learners An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15737188 ZenodoArchiveConcept: 15737187 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1124 2405685:WNGITGKP
Keywords: _r:AddedByMyEducationEvidence

Note de conseils sur la plateforme numérique - Messa, Angele; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2025)
This document is a guidance note on digital platforms, specifically focusing on e-learning and the use of Opale and Moodle software. It aims to support the implementation of a digital learning platform in Madagascar. The report addresses questions and challenges faced by the Ministry of National Education in developing and deploying digital educational content. It covers various aspects of e-learning, including evaluation methods, content structuring, accessibility, interactivity, and technical requirements. Key topics include different evaluation models, types of e-learning evaluation (formative and summative), guidelines for using Opale, tablet specifications for online learning, ensuring course accessibility, and using Moodle both online and offline. The document also provides a checklist for ensuring quality in e-learning course development and implementation. Keywords: e-learning; Moodle; Opale; digital platform; accessibility; usability; Madagascar Ce document est une note d’orientation sur les plateformes numériques, avec un accent particulier sur l’e-learning et l’utilisation des logiciels Opale et Moodle. Il vise à soutenir la mise en place d’une plateforme d’apprentissage numérique à Madagascar. Le rapport aborde les questions et défis rencontrés par le Ministère de l’Éducation Nationale dans le développement et le déploiement de contenus éducatifs numériques. Il traite de divers aspects de l’e-learning, notamment les méthodes d’évaluation, la structuration des contenus, l’accessibilité, l’interactivité et les exigences techniques. Les principaux sujets incluent les différents modèles d’évaluation, les types d’évaluation en e-learning (formative et sommative), les recommandations pour l’utilisation d’Opale, les spécifications des tablettes pour l’apprentissage en ligne, l’accessibilité des cours et l’utilisation de Moodle en mode en ligne et hors ligne. Le document propose également une liste de contrôle pour garantir la qualité du développement et de la mise en œuvre des cours en e-learning. Mots clés: e-learning; Moodle; Opale; platforme numériques; accessibilité; usabilité; Madagascar An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14995952 ZenodoArchiveConcept: 14995951 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7303773 10.53832/edtechhub.1101 2405685:RMJK6G6Q
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

EdTech for Girls' Education: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; D'Rozario, Jonny; Thinley, Sangay; Mazari, Haani; Hinks, Jessica (EdTech Hub, 2025)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for girls in Southeast Asia. The review summarises how EdTech is currently being used with girls in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech for girls' education. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for girls, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for girls. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10987856 ZenodoArchiveConcept: 10987855 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1022 10.53832/edtechhub.1086 2405685:QEHJZIUB 2405685:S4V6PXXU

Equality of Usage of Personalised Learning Software: Key Findings from EdTech Hub and EIDU’s Sandbox in Kenya - Rahman, Asad; Tanveer, Rabia; Olwala, Tess; Musungu Ongadi, Allan; Freidberg, Aidan; Munialo, Indrah (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14525520 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1081 ZenodoArchiveConcept: 14525519
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

The Use of Interactive Whiteboards to Support Refugee Learning - Ramesh Vasudevan, Sharanya; Handigol, Apoorva (EdTech Hub, 2025)
This EdTech Hub rapid scan outlines the efficacy of interactive whiteboards (IWBs) to better understand the potential impact of investment in the digitisation of teaching and learning materials to enhance access to education and learning for refugee children. The focus is on research that can highlight any evidence on the efficacy of interactive whiteboards in low- and middle-income country (LMIC) contexts characterised by high numbers of school-age refugees, with Turkey as a key case study. The scan highlights important and valid considerations that can be applied to broader learnings around IWBs. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15692961 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1123 ZenodoArchiveConcept: 15692960
Keywords: _r:AddedByMyEducationEvidence

Guide pour les utilisateurs de la tablette et de la plateforme Formation À Distance - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo (EdTech Hub, 2025)
This is a practical guide for users of a tablet for the distance learning platform (FAD), specifically for 2000 primary teachers in Madagascar. It covers: Tablet Basics: How to use the tablet, buttons, screen, touch controls, navigation, and settings. Accessories: Information on the solar charger / power bank and mini-speaker. Communication: Instructions on making calls, sending SMS and emails, and accessing the internet. Applications: Guides for using applications for training content and exercises. Online Platform: Instructions for accessing and using the Moodle online platform for assessments and resources. Tablet Care: Tips for protecting the tablet and optimizing battery life. The guide is intended for beginners and provides step-by-step instructions with illustrations. It also includes a list of abbreviations and acronyms. Keywords: teacher professional development; Madagascar; Moodle; tablet; user guide Ceci est un guide pratique destiné aux utilisateurs d’une tablette pour la plateforme d’apprentissage à distance (FAD), spécifiquement conçu pour 2000 enseignants du primaire à Madagascar. Il couvre : Bases de la tablette : Utilisation de la tablette, boutons, écran, commandes tactiles, navigation et paramètres. Accessoires : Informations sur le chargeur solaire/batterie externe et le mini-haut-parleur. Communication : Instructions pour passer des appels, envoyer des SMS et des e-mails, et accéder à Internet. Applications : Guides d’utilisation des applications pour les contenus de formation et les exercices. Plateforme en ligne : Instructions pour accéder et utiliser la plateforme Moodle pour les évaluations et les ressources. Entretien de la tablette : Conseils pour protéger la tablette et optimiser l’autonomie de la batterie. Ce guide est destiné aux débutants et propose des instructions pas à pas avec illustrations. Il comprend également une liste d’abréviations et d’acronymes. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les utilisateurs An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230784 ZenodoArchiveConcept: 14230783 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1066 10.53832/edtechhub.1073
Keywords: _r:AddedByMyEducationEvidence

Rapport d’Observation du Testing BETA - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo (EdTech Hub, 2025)
This is a report on the Beta testing of a digital learning platform and applications developed for the Ministry of Education in Madagascar. The project aims to train 16,000 teachers, with 2,000 utilising distance learning via tablets. The Beta user testing focused on the pedagogical relevance, usability, and ergonomics of the platform and two offline applications. Twenty-one teachers participated, evaluating tasks like launching applications, navigating content, accessing multimedia, and completing exercises / evaluations. Results showed significant improvement from the Alpha user testing, with high success rates for accessing and navigating modules. However, over 50% of users still found the platform difficult to use, particularly for login, navigation, and profile modification. The applications were generally functional but needed adjustments to content presentation and visual quality. Recommendations included simplifying the platform's interfaces, enhancing user guides, and addressing specific content issues. The document emphasises the importance of ongoing quality assurance and an iterative approach to refining the platform. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce rapport porte sur le test Beta d’une plateforme d’apprentissage numérique et des applications développées pour le Ministère de l’Éducation à Madagascar. Le projet vise à former 16 000 enseignants, dont 2 000 via l’apprentissage à distance sur tablette. Les tests utilisateurs en phase Beta ont évalué la pertinence pédagogique, l’ergonomie et la convivialité de la plateforme ainsi que de deux applications hors ligne. Vingt et un enseignants ont participé, réalisant des tâches telles que le lancement des applications, la navigation dans les contenus, l’accès aux éléments multimédias et la réalisation d’exercices/évaluations. Les résultats montrent une amélioration significative par rapport aux tests Alpha, avec des taux de réussite élevés pour l’accès et la navigation dans les modules. Cependant, plus de 50 % des utilisateurs ont encore rencontré des difficultés, notamment pour la connexion, la navigation et la modification du profil. Les applications étaient globalement fonctionnelles, mais nécessitaient des ajustements dans la présentation des contenus et la qualité visuelle. Les recommandations incluent la simplification des interfaces de la plateforme, l’amélioration des guides utilisateurs et la correction de problèmes spécifiques liés aux contenus. Le document souligne l’importance de l’assurance qualité continue et d’une approche itérative pour affiner la plateforme. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230760 ZenodoArchiveConcept: 14230759 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1058 10.53832/edtechhub.1072
Keywords: _r:AddedByMyEducationEvidence

Rapport d’Observation du Testing Alpha - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo; Koomar, Saalim (EdTech Hub, 2025)
This document, details the Alpha user testing of a digital learning platform and educational applications for the Ministry of National Education of Madagascar, aimed at training 2000 teachers. Conducted in July 2024, the testing focused on functionality and accessibility. Twenty-nine testers, primarily web developers and instructional designers, used a Google Forms questionnaire to evaluate the platform and applications. The results showed that while the platform was generally functional, with most features validated, several areas needed adjustments, particularly in accessibility and specific functions like the quiz timer. The applications had more issues, with several features requiring fixes and accessibility being a significant concern. Key recommendations included diagnosing and fixing defective parts, restructuring modules for better accessibility, optimising multimedia file sizes, and creating a detailed user guide. The testing highlighted the need for improvements before the Beta testing phase with teachers. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce document détaille les tests utilisateurs en phase Alpha d’une plateforme d’apprentissage numérique et d’applications éducatives développées pour le Ministère de l’Éducation Nationale de Madagascar, dans le cadre de la formation de 2 000 enseignants. Réalisés en juillet 2024, ces tests ont porté sur la fonctionnalité et l’accessibilité. Vingt-neuf testeurs, principalement des développeurs web et des concepteurs pédagogiques, ont évalué la plateforme et les applications via un questionnaire Google Forms. Les résultats ont montré que, bien que la plateforme soit globalement fonctionnelle avec la plupart des fonctionnalités validées, plusieurs ajustements étaient nécessaires, notamment en matière d’accessibilité et pour certaines fonctions spécifiques comme le minuteur des quiz. Les applications présentaient davantage de problèmes, plusieurs fonctionnalités nécessitant des corrections et l’accessibilité étant un défi majeur. Les principales recommandations incluaient le diagnostic et la correction des éléments défectueux, la restructuration des modules pour une meilleure accessibilité, l’optimisation de la taille des fichiers multimédias et la création d’un guide utilisateur détaillé. Ces tests ont mis en évidence la nécessité d’améliorations avant la phase de test Beta avec les enseignants. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230731 ZenodoArchiveConcept: 14230730 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1035 10.53832/edtechhub.1071
Keywords: _r:AddedByMyEducationEvidence

Enquête nationale sur la possession et les usages des technologies parmi les enseignants du primaire - Rasolohery, Hasiniavo; Mitchell, Joel (EdTech Hub, 2025)
This document presents a report of a national survey on technology ownership and usage among primary school teachers in Madagascar, conducted in 2023. The survey, a collaboration between EdTech Hub, the National Institute of Pedagogical Training (INFP), and the Ministry of National Education, aimed to gather reliable data on ICT deployment across Madagascar's 23 regions. Data was collected through quantitative surveys and qualitative focus groups involving 1403 educators. Key findings reveal that while 97% of educators own technological tools, basic mobile phones are most prevalent. Smartphone ownership is significant, but usage is largely limited to calls and SMS, indicating underutilisation of advanced features. Internet access is limited, with only 25.2% of teachers accessing it via smartphone. Electricity access is relatively high at 89%, primarily through the national grid and solar energy. The report highlights the need for ICT training to enhance teachers' digital skills and recommends deploying offline systems to overcome connectivity issues. It also emphasises adapting content for teachers with disabilities and considering the predominantly regional language usage in professional settings. Keywords: national teacher survey; technology access; technology use; Madagascar; primary school Ce document présente un rapport sur une enquête nationale menée en 2023 sur la possession et l’usage des technologies par les enseignants du primaire à Madagascar. Cette enquête, réalisée en collaboration entre EdTech Hub, l’Institut National de Formation Pédagogique (INFP) et le Ministère de l’Éducation Nationale, visait à recueillir des données fiables sur le déploiement des TIC dans les 23 régions du pays. Les données ont été collectées à travers des enquêtes quantitatives et des groupes de discussion qualitatifs impliquant 1 403 enseignants. Les résultats clés révèlent que, bien que 97 % des enseignants possèdent des outils technologiques, les téléphones mobiles basiques sont les plus répandus. La possession de smartphones est significative, mais leur utilisation se limite principalement aux appels et aux SMS, ce qui indique une sous-utilisation des fonctionnalités avancées. L’accès à Internet reste limité, avec seulement 25,2 % des enseignants l’utilisant via un smartphone. L’accès à l’électricité est relativement élevé (89 %), principalement via le réseau national et l’énergie solaire. Le rapport souligne la nécessité d’une formation aux TIC pour améliorer les compétences numériques des enseignants et recommande le déploiement de systèmes hors ligne pour pallier les problèmes de connectivité. Il met également l’accent sur l’adaptation des contenus aux enseignants en situation de handicap et sur la prise en compte de l’usage majoritaire des langues régionales dans les environnements professionnels. Mots clés: enquête nationale des enseignants; accès à technologie; utilisation de technologie; Madagascar; Moodle; école primaire An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14995637 ZenodoArchiveConcept: 14995636 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7997034 10.5281/zenodo.7997057 10.5281/zenodo.8401936 10.53832/edtechhub.1100 2405685:4MWP8553 2405685:5DJ69UTD
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Guide pour les administrateurs de la plateforme Formation À Distance - Rasolohery, Hasiniavo; Ranaivosamoelina, Tokiniaina (EdTech Hub, 2025)
This is a practical guide for administrators of the Formation À Distance (FAD) platform in Madagascar. The guide provides instructions on managing the platform, with a focus on evaluations and forums. It covers topics such as setting up different types of evaluations (quizzes, assignments), configuring forum settings, managing discussions, and moderating forums. It also includes best practices for both evaluations and forums, as well as security considerations. The document provides step-by-step instructions with screenshots for specific tasks like activating edit mode, adding activities or resources, setting up tests, and configuring forum parameters. It also includes a glossary of terms, references, and useful links. The guide is intended to help administrators effectively manage the FAD platform and support teachers and students in their online learning activities. Keywords: teacher professional development; Madagascar; Moodle; tablet; administrator guide Ceci est un guide pratique destiné aux administrateurs de la plateforme de Formation À Distance (FAD) à Madagascar. Il fournit des instructions pour la gestion de la plateforme, en mettant l’accent sur les évaluations et les forums. Il couvre des sujets tels que la configuration des différents types d’évaluations (quiz, devoirs), le paramétrage des forums, la gestion des discussions et la modération des forums. Il inclut également les meilleures pratiques pour les évaluations et les forums, ainsi que des considérations de sécurité. Le document propose des instructions détaillées, illustrées par des captures d’écran, pour des tâches spécifiques comme l’activation du mode édition, l’ajout d’activités ou de ressources, la mise en place de tests et le paramétrage des forums. Il comprend également un glossaire des termes, des références et des liens utiles. Ce guide vise à aider les administrateurs à gérer efficacement la plateforme FAD et à soutenir les enseignants et les élèves dans leurs activités d’apprentissage en ligne. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les administrateurs An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230806 ZenodoArchiveConcept: 14230805 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1062 10.53832/edtechhub.1074
Keywords: _r:AddedByMyEducationEvidence

Designing Digital Notifications to Support Teacher Uptake of Data Dashboards - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the fourth in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the extent to which the provision of notifications to pre-primary teachers to view data dashboards impacts learner device usage and learning outcomes. The A/B/C test found no impact on device usage and negligible impact on learning outcomes. This suggests that accompanying data dashboards with notifications did not influence pedagogical practice in a way which impacted on learning. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; notification system An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117643 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1049 ZenodoArchiveConcept: 13117642
Keywords: _r:AddedByMyEducationEvidence

Investigating the Impact of Content Repetition on Digital Personalised Learning Tools for Early Grade Learners - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the third in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the impact of repeating learning content for pre-primary learners on learner device usage and learning outcomes. The A/B test found that content repetition had an impact on literacy and numeracy outcomes for PP2 learners. PP2 learners’ usage of the DPL tool was significantly reduced with content repetition. However, considering the small size of the mixed-methods sample, caution should be taken when interpreting these results. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; repetition An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117639 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1048 ZenodoArchiveConcept: 13117638
Keywords: _r:AddedByMyEducationEvidence

Testing Digital Timer Tools to Support Early Grade Lesson Delivery - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the second in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates whether introducing a timer alongside digitised lesson plans impacts upon teachers’ lesson plan usage. The A/B test found that providing a timer did not influence how much time teachers spent on digitised lesson plans. While, on average, teachers in the timer group tended to spend less time on lesson plans for literacy and more for numeracy, this was not statistically significant. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; timer; lesson plan An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117635 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1047 ZenodoArchiveConcept: 13117634
Keywords: _r:AddedByMyEducationEvidence

Optimising Session Duration on Digital Personalised Learning Tools for Early Grade Learners - Sun, Chen; Moustafa, Nariman; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the first in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the optimal number of minutes for pre-primary learners on a classroom-integrated digital personalised learning tool to optimise learning outcomes. The A/B/C test found different levels of session duration impacted on literacy and numeracy outcomes, with the findings for numeracy dependent on grade level. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; session duration An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117631 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1046 ZenodoArchiveConcept: 13117630
Keywords: _r:AddedByMyEducationEvidence

Cross Cutting Themes - Swindell, Andrew (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15270303 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1111 ZenodoArchiveConcept: 15270302
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

One Teacher Thailand: A case study of a teacher learning network - Thang, Sarah; Thinley, Sangay; Wiboonuppatum, Rangsun; Saihjee, Aarti; Khlaisang, Jintavee; Thammetar, Thapanee; Kaosaiyaporn, Ophat; Saiyasit, Pichsinee; Theeraroungchaisri, Natchapat (EdTech Hub, 2025)
This case study explores One Teacher Thailand (OTT), a teacher-led learning network that supports holistic professional development rooted in the real needs of classrooms. Driven by a core team of volunteer teacher leaders, OTT integrates educational technology with broader concerns such as mental health, safety, and student engagement. The report examines the network’s evolution, identifies key factors behind its success, and offers recommendations to guide its continued growth and scaling across Thailand. Keywords: teacher networks; Thailand; peer learning; teacher leadership; teacher professional development A version of this report in Thai has been published by UNICEF and available by following the link to this provided with this record below. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14172051 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1069 ZenodoArchiveConcept: 14172050
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13256782 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1053 ZenodoArchiveConcept: 13256781
Keywords: _r:AddedByMyEducationEvidence

What is Tech Winter? Know understanding, cause, and impact for startup companies - VOI Editorial Team (VOI - Waktunya Merevolusi Pemberitaan, 2025)
What is a tech winger? Tech winger is a period where there is a significant decline in the technology industry...
KerkoCite.ItemAlsoKnownAs: 2339240:LWNICYBR 2405685:N5TUQ7B8

Ukraine Conflict: An overview - Mills, Claire (UK Parliament, House of Commons Library, 2025)
Russia's invasion of Ukraine marked its third anniversary on 24 February 2025.
KerkoCite.ItemAlsoKnownAs: 2339240:YJLHN4FA 2405685:DJKU46LL
Keywords: ⛔ No DOI found

Pakistan floods and cloudbursts visualised in maps and satellite images - Ali, Marium (Al Jazeera, 2025)
Heavier than usual rains and sudden cloudbursts during this monsoon season kill more than 300 people in recent days.
KerkoCite.ItemAlsoKnownAs: 2339240:G94INENN 2405685:58KWMMBG

Ukraine: Education Cluster Response, January - June 2025 - Education Cluster; Save the Children; UNICEF (2025)
Infographic in English on Ukraine about Education and Protection and Human Rights; published on 14 Aug 2025 by Education Cluster, Save the Children and 2count other organizations
KerkoCite.ItemAlsoKnownAs: 2339240:HGNKNF6Z 2405685:AXTYW64T

Oblasts of Ukraine - Wikipedia (Wikipedia, 2025)
An oblast (Ukrainian: область, romanized: oblast, pronounced [ˈɔblɐsʲtʲ] ; pl. області, oblasti), sometimes translated as region or province, is the main type of first-level administrative division of Ukraine. The country's territory is divided into 24 oblasts, as well as one autonomous republic and two cities with special status. As Ukraine is a unitary state, oblasts do not have much legal scope of competence other than that which is established in the Ukrainian Constitution and devolved by law. Articles 140–146 of Chapter XI of the constitution deal directly with local authorities and their competence. Oblasts are divided into raions, with each oblast having between three and eight raions following the July 2020 reform.
Page Version ID: 1300391496 KerkoCite.ItemAlsoKnownAs: 2405685:KHA9VALU

EdTech Hub: Transforming learning through evidence - Results for Development (Results for Development, 2025)
A global initiative led by R4D and partners that gives education decision-makers the evidence they need to use technology to transform education in low-and middle-income countries.
KerkoCite.ItemAlsoKnownAs: 2339240:B4W73MP8 2405685:P4L2YUZ7

Over a thousand schools have connected to the "Mriya" educational platform - Ukrainian National News (Ukrainian National News (UNN), 2025)
УНН Technologies ✎ Over 1,300 Ukrainian schools have joined the national educational platform "Mriya." This exceeded initial expectations, improving parental interaction…
KerkoCite.ItemAlsoKnownAs: 2339240:9F92YRWX 2405685:B46UJCB5

Budget 2025-26 from a climate lens - Naeem, Zainab (2025)
By any measure, Pakistan’s federal budget for FY2025-26 represents a notable evolution in the country's approach to climate change.For a country that has endured some of the most brutal...
KerkoCite.ItemAlsoKnownAs: 2339240:X5PCSL7E 2405685:WTLI8KHH

Climate Risk Index 2025 - Germanwatch (2025)
The Climate Risk Index (CRI) ranks countries by the human and economic toll of extreme weather. The latest edition highlights increasing losses and the urgent need for stronger climate resilience and action.
KerkoCite.ItemAlsoKnownAs: 2339240:EDR92U2P 2405685:7Z8KVUL9

UNICEF Annual Report 2024 - UNICEF (2025)
Staying and delivering for children
KerkoCite.ItemAlsoKnownAs: 2339240:7NZ6YB8V 2405685:SSXVB98B

CATCH by GoGlobal is now on the All-Ukrainian Online School: The first recovery learning program in Ukraine for primary school students is now available to every teacher - GoGlobal (2025)
The first recovery learning program in Ukraine for primary school students is now available to every teacher
KerkoCite.ItemAlsoKnownAs: 2339240:LK42IAXV 2405685:TKMEXFQ6

Evaluating the Learner Experience of the TCPD Learning Management System for Primary School Teachers in Tanzania - Kondoro, Aron; Maro, Salome; Mtebe, Joel; Simmons, Hannah; Komba, Aneth (2025 IST-Africa Conference (IST-Africa), 2025)

Self-directed learning and student-centred learning: A conceptual comparison - Morris, Thomas Howard; Bremmer, Nicholas; Sakata, Nozomi (Pedagogy, Culture & Society, 2025)
Self-directed learning and student-centred learning are key theoretical constructs in the educational literature. However, to date, the similarities and differences between these terms have not been examined. This paper therefore provides a historical overview of both constructs, followed by an analysis of the similarities and differences between them. The analysis found that student-centred learning has been interpreted in a much broader and more inconsistent way than self-directed learning, and that any conceptual comparison is dependent on the ways in which student-centred learning is interpreted. In particular, the inclusion or non-inclusion of the notion of power-sharing is key when comparing student-centred learning to self-directed learning. If power-sharing is not considered part of student-centred learning, learning might be student-centred and not yet self-directed. An original and important conclusion from the present work is that: only if power-sharing is considered part of student-centred learning can learning be both student-centred and self-directed. Increased clarity around the meanings of these concepts will benefit teachers and other educational stakeholders and will allow us to conduct more valid research to examine the potential impacts of such approaches.
Publisher: Routledge _eprint: https://doi.org/10.1080/14681366.2023.2282439 KerkoCite.ItemAlsoKnownAs: 10.1080/14681366.2023.2282439 2339240:LH3UVNIV 2405685:WUC5U4T5

Program Deep Learning Ruangguru untuk Siapkan Sekolah Hadapi TKA & UTBK - Ruangguru (Ruangguru, 2025)
KerkoCite.ItemAlsoKnownAs: 2339240:6TQNYEEF 2405685:P4DGMXS3

New data: Progress and challenges for the education of displaced pupils from Ukraine in Europe | European School Education Platform - UNESCO (2025)
A new interagency dashboard led by UNESCO is offering key data on the education of displaced Ukrainian children across host countries in Europe. It was built in cooperation with UNHCR, the EU, UNICEF, OECD and the Council of Europe.
KerkoCite.ItemAlsoKnownAs: 2339240:UBA4UNHY 2405685:F5TFUKRK

Call for Saudis to join national AI training - Arab News (Arab News, 2025)
RIYADH: The Saudi Data and AI Authority, in collaboration with the education and human resources and social development ministries, has invited citizens to register for the national initiative, “One Million Saudis in AI – SAMAI.” The initiative, which is taking place for the first time, aims to train 1 million Saudis in artificial intelligence to strengthen national capabilities in line with Vision 2030, the Saudi Press Agency reported on Wednesday.
KerkoCite.ItemAlsoKnownAs: 2405685:EPKYBRFL

The All-Ukrainian Online School - hundrED (2025)
The All-Ukrainian Online School ensures uninterrupted learning for millions of Ukrainian students affected by war and displacement. This national digital platform delivers free, curriculum-aligned content created by expert teachers, offering a scalable, inclusive solution for hybrid and remote education.
KerkoCite.ItemAlsoKnownAs: 2339240:MY7ZMDHR 2405685:XM7NQ9PF

EdTech funding drops again in early 2025. Fewer deals, but bigger bets - HolonIQ (2025)
$410M in Global EdTech VC funding with fewer deals, larger checks, and new regional momentum hint at where investment is heading next.
KerkoCite.ItemAlsoKnownAs: 2339240:VIYEGZ9Y 2405685:JFBLFFJF

Mriya: Ukraine's innovative educational ecosystem - Government of Ukraine (2025)
Mriia is revolutionizing education in Ukraine by integrating personalized learning, simplifying administration, and offering real-time progress tracking to students, teachers, and parents
KerkoCite.ItemAlsoKnownAs: 2339240:T2RTLVA6 2405685:2KZQFIJX

Ukraine launches digital educational platform “Mriia” nationwide for all schools - Litnarovych, Vlad (UNITED24 Media, 2025)
Ukrainian President Zelenskyy announces Mriia, an AI-based educational platform, is now accessible to all schools, enhancing digital learning nationwide.
KerkoCite.ItemAlsoKnownAs: 2339240:V2GMVYYS 2405685:TWNYUYTN

One Teacher Thailand: A case study of a teacher learning network - Thang, Sarah; Thinley, Sangay; Wiboonuppatum, Rangsun; Saihjee, Aarti; Khlaisang, Jintavee; Thammetar, Thapanee; Kaosaiyaporn, Ophat; Saiyasit, Pichsinee; Theeraroungchaisri, Natchapat (UNICEF and EdTechHub, 2025)
กรณีศึกษาเครือข่ายครู ประเทศไทย

Kenya: Registered refugees and asylum-seekers as of 31 March 2025 - UNHCR (UNHCR Kenya, 2025)
KerkoCite.ItemAlsoKnownAs: 2339240:WI34EICY 2405685:7ZNKUUAL

Ukraine Education Cluster Strategy 2025 - Education Cluster; Save the Children (2025)
Manual and Guideline in English on Ukraine about Coordination, Education and more; published on 25 Mar 2025 by Education Cluster, Save the Children and 2count other organizations
KerkoCite.ItemAlsoKnownAs: 2339240:NW7AKTES 2405685:GDMDE37N

Critical perspectives on the use of technology with refugees and displaced communities: The case of Dadaab - Leomoi, Ochan (Journal of Interactive Media in Education, 2025)
Dadaab Refugee Complex hosts refugees from the Horn of Africa and the Great Lakes region. According to a UNHCR (2023) report, at 31 January 2023 Dadaab refugee camps were host to a total population of 233,828 registered refugees and asylum seekers, representing 41% of the total recognized forcibly displaced people in Kenya. This paper will explore Dadaab as the context for connected learning in addition to the author’s first-hand accounts. The author provides a reflexive account of the perspectives of refugees in Dadaab refugee camps and Dadaab host-communities on the role of higher education for individual and social transformation, and how technology could be embraced to leverage learning despite challenges to the access and use of the internet, and computers. In this paper, the author makes a reflexive account of the role of education in transforming refugee learners and communities, and how technology was employed, albeit with challenges, to connect Dadaab with other higher education institutions within and beyond Kenya’s boundaries. The author is further concerned with how technology in higher education in crisis contexts is conceived as the agent that builds networks of scholars, generates connections for development, and promotes exchange of knowledge and ideas among students and faculty across all geographical borders.
KerkoCite.ItemAlsoKnownAs: 10.5334/jime.875 2339240:EFGCPSD5 2405685:4AT8APK7

Uneven Adoption of Artificial Intelligence Tools Among U.S. Teachers and Principals in the 2023–2024 School Year - Kaufman, Julia H.; Woo, Ashley; Eagan, Joshua; Lee, Sabrina; Kassan, Emma B. (RAND Corporation, 2025)
Drawing on nationally representative survey data, the authors examine the use of artificial intelligence (AI) tools and products among teachers and principals and the presence of school policies on the use of AI during the 2023–2024 school year. Their findings provide useful information for those who support teachers at the school, district, and state levels, as well as providers and developers of AI tools for use by teachers and students.
KerkoCite.ItemAlsoKnownAs: 2339240:4LL7TYHD 2405685:59D3L4PT
Keywords: Alumni; Artificial Intelligence; Education Curriculum; Educational Technology; Principals; Research; Students; Teachers and Teaching

Transforming general upper secondary education in Ukraine: Insights from international experiences - OECD (OECD Publishing, 2025)
KerkoCite.ItemAlsoKnownAs: 10.1787/7c357ac4-en 2339240:ZYSFK99F 2405685:5LF3LIEA

Attacks on education in Ukraine double in 2024, leaving some parents terrified to send their children to school - Save the Children (Save the Children International, 2025)
New analysis, released on the eve of International Day of Education, shows 576 education facilities in Ukraine – including schools, kindergartens and universities – were damaged or destroyed in 2024 compared to 256 education facilities in 2023.
KerkoCite.ItemAlsoKnownAs: 2339240:ZHAWI5AU 2405685:R63LTVJI

Gallup Data Analytics series on Pakistan Social and Living Standards Measurement data - Gallup Pakistan (2025)
Gallup Pakistan, the Pakistani affiliate of Gallup International, is a leading survey research and consultancy firm in Pakistan. Gallup Pakistan is a specialist in independent third-party evaluation and ratings. The company is widely attributed to be the founder of science of polling in Pakistan and brings over 40 years of experience in conducting and analyzing opinion polling in Pakistan.
KerkoCite.ItemAlsoKnownAs: 2339240:Q7W6J9KP 2405685:V52YRQDT

World Bank makes 10-year plan with Pakistan for $20 billion in funding - Greenfield, Charlotte (Reuters, 2025)
Pakistan's prime minister on Wednesday welcomed a first-of-its-kind agreement with the World Bank for a plan to focus $20 billion in lending to the cash-strapped nation over the coming decade on development issues like the impact of climate change as well as boosting private-sector growth.
KerkoCite.ItemAlsoKnownAs: 2339240:IEVRB2UX 2405685:EKIYR8C8

Interactive whiteboard as a medium for Nahwu learning: Bridging technology and Arabic grammar education - Masnun; Baharun, Segaf; Syakur, Sultan Abdus (International Journal of Arabic Language Teaching, 2025)
People who have mastered Nahwu often struggle to adjust to using technology. This research investigates the integration of Interactive Whiteboards (IWBs) as a transformative tool in Nahwu (Arabic syntax) learning, addressing the longstanding challenges associated with traditional pedagogical approaches. The study emphasizes the unique contribution of IWBs in bridging the gap between traditional Nahwu instruction and technology-based learning by incorporating multimodal strategies, such as dynamic diagrams, real-time feedback, and interactive sentence-building exercises. These features not only enhance student engagement but also simplify the comprehension of intricate grammatical rules, making Nahwu more accessible to modern learners. The qualitative research involved 30 students and 5 educators from an Islamic boarding school, utilizing interviews, focus group discussions, classroom observations, and document analysis. Key findings demonstrate that IWBs significantly improve cognitive retention, student participation, and the overall effectiveness of Nahwu instruction. Practical recommendations include providing robust teacher training on IWB integration, designing interactive lesson plans tailored to the needs of Generation Z learners, and leveraging IWB capabilities to foster collaborative and inquiry-based learning environments. This study highlights IWBs as a cornerstone in modernizing Arabic grammar education, offering actionable insights for educators and institutions aiming to implement technology-driven teaching solutions effectively.
Number: 01 KerkoCite.ItemAlsoKnownAs: 10.32332/ijalt.v7i01.9977 2339240:EJG5ZJ3Y 2405685:ZYQCK9NI 6018420:7CHAY36P
Keywords: Arabic grammar; Nahwu learning; educational technology; interactive whiteboards; pedagogical innovation

Estimating the increase in emissions caused by AI-augmented search - Vanderbauwhede, Wim (arXiv, 2025)
AI-generated answers to conventional search queries dramatically increase the energy consumption. By our estimates, energy demand increase by 60-70 times. This is a based on an updated estimate of energy consumption for conventional search and recent work on the energy demand of queries to the BLOOM model, a 176B parameter model, and OpenAI's GPT-3, which is of similar complexity.
arXiv:2407.16894 [cs] KerkoCite.ItemAlsoKnownAs: 10.48550/arXiv.2407.16894 2405685:EK5IKETK
Keywords: Computer Science - Artificial Intelligence; Computer Science - Computers and Society

Forecast mostly gloomy, but that’s a good thing - Harford, Tim (Financial Times, 2025)
KerkoCite.ItemAlsoKnownAs: 2405685:MLK3MUZM

Bridging Educational Gaps Watching TV at Home: The Impact of an Educational TV Show on Kenyan Children - Baier, Jasmin; Barasa, Laura; Bottan, Nicolas; Ghosh, Anushka; Millrine, Mark (SSRN, 2025)
KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.5022687 2405685:646WWAJT

Integrating digital personalised learning into pre-primary classroom practice: A teacher-researcher multiple-case study partnership in Kenya - Daltry, Rebecca; Major, Louis; Otieno, Mary; Otieno, Kevin; Jordan, Katy; Moustafa, Nariman (Education Sciences, 2025)
KerkoCite.ItemAlsoKnownAs: 10.3390/educsci15060698 2339240:SSMTZDU2 2405685:6EKCYC9U 2405685:R9QWX9VA
Keywords: ⛔ No DOI found

Managing ADHD symptoms in children through the use of various technology-driven serious games: A systematic review - Doulou, Aikaterini; Pergantis, Pantelis; Drigas, Athanasios; Skianis, Charalampos (Multimodal Technologies and Interaction, 2025)
Children with attention deficit hyperactivity disorder (ADHD) frequently experience impairments in a range of abilities. Due to their poor attention and concentration, they find it challenging to stay focused when learning. They need help to retain the directions given by teachers and are very animated. Focus issues, hyperactivity, and attention problems may hamper learning. The needs and challenges of children with ADHD have been addressed by numerous digital solutions over the years. These solutions support a variety of needs (e.g., diagnosing versus treating), aim to address a variety of goals (e.g., addressing inattention, impulsivity, working memory, executive functions, emotion regulation), and employ a wide range of technologies, including video games, PC, mobile, web, AR, VR, tangible interfaces, wearables, robots, and BCI/neurofeedback, occasionally even in tandem. According to studies on the psychological impacts of serious games, immersive games can potentially be valuable tools for treating ADHD. This research investigates using PC, mobile/tablet applications, augmented reality, virtual reality, and brain–computer interfaces to develop executive functions and metacognitive and emotional competencies in children with ADHD through serious games. Following PRISMA 2020 criteria, this systematic review includes a comprehensive search of the PubMed, Web of Science, Scopus, and Google Scholar databases. The database search provided 784 records, and 30 studies met the inclusion criteria. The results showed that serious games assisted by multiple technologies could significantly improve a wide range of cognitive and socioemotional meta-competencies among children with ADHD, including visuospatial working memory, attention, inhibition control, cognitive flexibility, planning/organizing, problem-solving, social communication, and emotional regulation. The results of this review may provide positive feedback for creating more inclusive digital training environments for the treatment of ADHD children.
KerkoCite.ItemAlsoKnownAs: 10.3390/mti9010008 2339240:KFZES5RR 2405685:LAYFKGU3

Education Development Trust - Education Development Trust (2025)
Improving school systems at scale and provide empowering employability and careers services to young people and adults.
KerkoCite.ItemAlsoKnownAs: 2405685:2P88ECBH 2486141:SE98TW6X

Ukraine Conflict: ETC Situation Report #48 - Emergency Telecommunications Cluster (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:QY89W8EJ 2405685:QLV6DADG

EU solidarity with Ukraine - European Council (Consilium, 2025)
The EU is supporting Ukraine's economy, army and society. The EU is also welcoming Ukrainian refugees and is providing humanitarian aid and civil protection support.
KerkoCite.ItemAlsoKnownAs: 2339240:45LH4KLM 2405685:ZSE7Q5J8

Ukraine: Digital transformation of education as a strategic path to resilience and innovation - Eurydice (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:7YXDTY4Y 2405685:SC88J9KC

Ukraine: Early childhood and school education funding - Eurydice (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:2FII4CB3 2405685:ZSNNQH77

Ukraine Education System Overview - Eurydice (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:85CUW5PU 2405685:X5Z5QT3P

Ukraine: Organisation of the education system and of its structure - Eurydice (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:FTH3G2AD 2405685:2TUX8JU2

Ukraine - Global Education Cluster (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:KSRNDY42 2405685:4HFHUKYJ

Ukraine: Education brings mental health support to children - Global Partnership for Education (2025)
Read how GPE and partners are helping increase the capacity of Ukraine’s educators to provide children with mental health services.
KerkoCite.ItemAlsoKnownAs: 2339240:D3G3B248 2405685:N7KZDHL6

Home page - Government of Ukraine (State Service of Education Quality of Ukraine, 2025)
KerkoCite.ItemAlsoKnownAs: 2339240:8QK7WLXK 2405685:23ZIBGPU

Ukraine: Humanitarian Needs and Response Plan 2025. 2.8. Multipurpose Cash and Cash and Voucher Assistance Overview - Humanitarian Action (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:9DEQ3F6U 2405685:YBN27FWX

Ukraine: Humanitarian Needs and Response Plan 2025. 3.2. Education - Humanitarian Action (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:MRFPLRMA 2405685:RZ97NTPP

“Mriia. Post-Education”: The Major EdTech Event of the Year Organised by the Ministry of Digital Transformation and the Ministry of Education and Science (8 April 2025) - IEA (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:S44KS2H3 2405685:CRUD29HZ

Ukraine ITU DataHub - International Telecommunication Union (ITU DataHub, 2025)
KerkoCite.ItemAlsoKnownAs: 2339240:ETMUE48X 2405685:PS5WI3DG

An analysis of the impact of digital therapeutic interventions on attention and working memory in children with attention-deficit/hyperactivity disorder: A randomized controlled trial - Kim, Seon-Chil; Lee, Hojun (Applied Sciences, 2025)
Previous research has investigated non-pharmacological digital therapeutic interventions to improve compliance and reduce side effects in attention-deficit/hyperactivity disorder (ADHD) medication treatments for children. This study focuses on validating the effects of game-based intervention content for enhancing working memory and concentration. It tracks quantitative changes to evaluate improvements in concentration and working memory when digital game-based content is used as adjunct therapy alongside medication for children with ADHD. Thirty children participated; one group received digital therapeutic intervention based on game content alongside medication (experimental) and the other group received conventional treatments (control). The study results show that children with ADHD in the experimental group, who use digital game-based content, exhibit a reduction of 8.13 ± 6.71 points in the K-ARS total score at the fourth week compared to baseline, while the control group shows a reduction of 7.14 ± 8.73 points. Inattention decreases by 36.84% in the experimental group and 28.56% in the control group, while hyperactivity–impulsivity decreases by 50.71% in the experimental group and 34.00% in the control group. All the results are analyzed using a paired t-test between baseline and the fourth week. Significant decreases in the K-CBCL total problem behavior score and internalizing and externalizing behaviors are consistently observed at 28 days compared with baseline. The FAIR attention–concentration test results show significant differences between the experimental and control groups in the Q-percentile and Q-standard scores, with repeated measures ANOVA results showing p = 0.006 and p = 0.007, respectively. Digital content was shown to influence digital therapeutic intervention—a non-pharmacological treatment for ADHD.
KerkoCite.ItemAlsoKnownAs: 10.3390/app15020788 2339240:CV2NHMF4 2405685:8E9DPKGR

Diaa Ecosystem - Kyiv Global Government Technology Centre (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:NGPUZV38 2405685:JSCC5WU4

Embedding gender equality and social inclusion (GESI) in research with teachers: A self-assessment framework. - Lynch, Ingrid (Foundation for Information Technology Education and Development and Fundación SUMMA., 2025)
KerkoCite.ItemAlsoKnownAs: 2339240:44YHK9R3 2405685:SEBR6ZNM

Digital Ukrainian credentials accessible via Diia digital application - McKenna, Tatiana (National Association of Credential Evaluation Services, 2025)
KerkoCite.ItemAlsoKnownAs: 2339240:W4YR8UGC 2405685:PPPUZV9M

National Digital Learning Strategy for the Sierra Leone Ministry of Basic and Senior Secondary Education & Teaching Service Commission 2025–2030 - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2025)
Sierra Leone launches first-ever National Digital Learning Strategy The Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC) are pleased to announce the launch of Sierra Leone’s first-ever National Digital Learning Strategy (NDLS) — a groundbreaking framework aimed at leveraging educational technology to improve teaching and learning in Sierra Leone. Developed through a collaborative and consultative process with representatives from the MBSSE, TSC, Ministry of Tertiary and Higher Education (MTHE), Presidential Delivery Unit (PDU), and Ministry of Communications, Technology, and Innovation (MoCTI) and shaped by insights from students, teachers, district leaders and officials, the NDLS outlines key priorities related to addressing the digital divide in Sierra Leone; improving teachers’ digital capabilities; strengthening learners’ access to technology; improving access to localized content, and improving coordination mechanisms between all EdTech stakeholders. EdTech Hub is a proud partner of this work alongside the UK Foreign, Commonwealth and Development Office (FCDO), UNICEF, the World Bank, and other collaborators. This collaboration included technical guidance and support throughout the process. The NDLS represents a collective commitment to transforming education and building future-ready learners and educators.
KerkoCite.ItemAlsoKnownAs: 2405685:WVVB6PCG

500 laptops delivered to Ukrainian schools through the Device Coalition - Ministry of Education and Science of Ukraine (2025)
The global children’s charity Theirworld and the Olena Zelenska Foundation, in cooperation with the Ministry of Education and Science of Ukraine, have delivered 500 laptops to general secondary education institutions across the country
KerkoCite.ItemAlsoKnownAs: 2339240:DTYGAAL6 2405685:XCYU92FC

How to organize learning for Ukrainian children abroad: Q&A - Ministry of Education and Science of Ukraine (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:7XNSVGP6 2405685:HXY9RCYK

Ukraine Country Profile on School Network Optimisation - Ministry of Education and Science of Ukraine (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:EE6TBD8U 2405685:ZIR8PIPX

Ukraine: Recognition of schoolchildren’s learning outcomes acquired abroad is now regulated - Ministry of Education and Science of Ukraine (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:Q8G2BPYS 2405685:J9LPY999

Zavgorodnii Dmytro - Ministry of Education and Science of Ukraine (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:HAYS57VN 2405685:ALR3UDMV

Inclusive education through technology: A systematic review of types, tools and characteristics - Navas-Bonilla, Carmen del Rosario; Guerra-Arango, Julio Andrés; Oviedo-Guado, Daniel Alejandro; Murillo-Noriega, Daniel Eduardo (Frontiers in Education, 2025)
KerkoCite.ItemAlsoKnownAs: 10.3389/feduc.2025.1527851 2339240:3GVABJL7 2405685:T6NA6YTM

Ukraine's Education Policy as a Pillar for Successful Rebuilding - Nazarenko, Y (Foundation for European Progressive Studies, 2025)
KerkoCite.ItemAlsoKnownAs: 2339240:YN3T358C 2405685:IDAP767S

Looking Forward: The alliance of Ukrainian CSOs - Nicholas Noe (Refugees International, 2025)
The Alliance’s experience offers valuable insights for how locally led coalitions can drive power-shifting efforts as humanitarian aid diminishes.
KerkoCite.ItemAlsoKnownAs: 2339240:XYF8RNGU 2405685:HYPX5UQX

AI User Manual: For teachers, students, schools, and parents in Thailand 2025 - Office of Academic Affairs and Educational Standards; Office of the Basic Education Commission (OBEC) (Government of Thailand, 2025)
KerkoCite.ItemAlsoKnownAs: 2339240:TRCCWJEY 2405685:VW67FTL4

Three years of war in Ukraine: Education disruptions deepen mental health crisis for children - Plan International (Plan International EU Liaison Office, 2025)
Five consecutive years of disrupted schooling in Ukraine is having devastating consequences for children’s development and mental wellbeing, child rights NGO Plan International warns as the war enters its fourth year, calling for more support for pupils to continue their studies.
KerkoCite.ItemAlsoKnownAs: 2339240:GF6MUAEC 2405685:6GGQ629Q

Emotional trauma piles up for Ukraine's children three years after invasion - Reuters (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:7UGQIB8G 2405685:WBP4MSFL

Lost Lessons Due to Air Raid Alerts: How Many — and What Can Be Done? - Savisko, Myroslava; Karakai, Antonii (Vox Ukraine, 2025)
How many hours of classroom time have Ukrainian students lost due to air raid alerts? Which regions have experienced the...
KerkoCite.ItemAlsoKnownAs: 2339240:AMEXYGKY 2405685:QQFH8BEY

How the state provides Ukrainian children abroad with access to education: Results of the accounting chamber of Ukraine audit - The Accounting Chamber (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:BT4JNB8A 2405685:YDRLUS2N

Remedial Education Programmes in Ukraine: Best practices and practical recommendations - Ukraine Education Cluster (2025)
Manual and Guideline in English on Ukraine about Education; published on 1 May 2025 by Education Cluster and UNICEF
KerkoCite.ItemAlsoKnownAs: 2339240:7X4KFMX7 2405685:69SEZ9BI

Minutes of NSC Meeting 30.04.25 - Ukraine Shelter Cluster (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:8U98L7SQ 2405685:ZWLQ4I6Z

About Us | UCEQA - Ukrainian Center for Educational Quality Assessment (2025)
The Ukrainian Center for Educational Quality Assessment (UCEQA) is a state institution that delivers external independent evaluation of students’ learning outcomes at a certain educational level, and conducts monitoring studies of the quality of education in Ukraine.
KerkoCite.ItemAlsoKnownAs: 2339240:4QX8X7Y7 2405685:NN3NTJ3W

Education for Ukrainian refugee learners in European host countries - UNESCO (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:7DBKVBLZ 2405685:AWPQYLE4

Education in emergencies: what you need to know - UNESCO (2025)
What UNESCO does where crises and attacks affect education
KerkoCite.ItemAlsoKnownAs: 2339240:I8US35UR 2405685:CTFVW3PE

Project: GPE System Capacity Grant for Strengthening Education Sector Capacity to Facilitate Access to Quality Education Service Delivery in Afghanistan details | Core Data Portal - UNESCO (2025)
Strengthening Education Sector Capacity to Facilitate Access to Quality Education Service Delivery in Afghanistan is funded by the Global Partnership for Education through its System Capacity Grant. UNESCO leads the overall program design, implementation, M&E and reporting as the Grant Agent. USAID and FCDO are the Coordinating Agencies. Key outputs of the project include an updated Afghanistan Education Sector Transitional Framework for 2024-2025, improved coordination mechanism between humanitarian and development partners for information sharing, joint programming and emergency responses, M&E and reporting, improved operational capacity of national sub-national partners.
KerkoCite.ItemAlsoKnownAs: 2339240:AVN322T4 2405685:EG6CJLAS

Public–private partnerships to bridge gaps in education continuity in times of crises: the Ukraine case study - UNESCO (2025)
The report developed by UNESCO's Global Education Coalition in collaboration with KPMG International, highlights the enriching collaborative experience between the public and the private sector in Ukraine, showcasing the positive and sustainable impact of its initiatives on the national education system and the additional opportunities that can be unlocked through partnership.
KerkoCite.ItemAlsoKnownAs: 2339240:J4XIF7VV 2405685:EC5FBRLD

Understanding the needs of Ukrainian Teacher Training Institutions - UNESCO (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:ZENPX7ZL 2405685:G8HHDH2H

New data insights reveal both progress and challenges for Ukrainian refugee students’ education in Europe - UNHCR (UNHCR Europe, 2025)
UNHCR, the UN Refugee Agency, in collaboration with members of the Regional Technical Hub on Refugee Education (including UNHCR, UNESCO, UNICEF, the EU, OECD, and Council of Europe), has launched a data dashboard that consolidates key data, policy and support measures, and evidence on education for Ukrainian refugees in European host countries.
KerkoCite.ItemAlsoKnownAs: 2339240:8X2IYVH6 2405685:DABUFJDP

4.6 million children in Ukraine face ongoing educational barriers as fourth academic year during war begins - UNICEF (2025)
Children start another school year during wartime and ahead of the coming freezing winter months, but despite challenges they are determined to learn with support from dedicated educators across the country.
KerkoCite.ItemAlsoKnownAs: 2339240:M9YU7EWP 2405685:8M7TXQM9

Catch-up classes help conquer barriers to education in Ukraine - UNICEF (2025)
Eight-year-old Liana, from Ukraine’s Dnipro region, eagerly attends catch-up lessons at her local digital learning centre.
KerkoCite.ItemAlsoKnownAs: 2339240:NAAQWTI4 2405685:38KYTEJG

Disability Inclusion in UNICEF Activities in Ukraine 2022-2024 - UNICEF (2025)
From 2022 to 2024, as part of the humanitarian response to the war in Ukraine, all United Nations Children’s Fund (UNICEF) sections implemented projects and led activities that impacted families with children with disabilities.
KerkoCite.ItemAlsoKnownAs: 2339240:3579IFBT 2405685:M3CZ2ZLV

Ukraine Humanitarian Situation Report No. 49 - UNICEF (2025)
KerkoCite.ItemAlsoKnownAs: 2339240:GHZTSQ6L 2405685:GHEJTXSF

Diia.Education launches updated digital map with Digital Education Hubs - United Nations Development Programme (UNDP, 2025)
From now on, members of the public will be able to quickly find the nearest hub where they can master essential digital skills.
KerkoCite.ItemAlsoKnownAs: 2339240:LSUHX26Z 2405685:GA5ALX4J

State Digital Transformation in Ukraine: 2019–2024 Review - Vyhovska, Viktoriia; Sholudko, Viktor; Balytska, Mariia (Vox Ukraine, 2025)
Digital transformation in Ukraine is a systemic process that has encompassed nearly all areas of public administration. The innovation behind...
KerkoCite.ItemAlsoKnownAs: 2339240:KFFQSPB6 2405685:LUFR546N

Ukraine - Fourth Rapid Damage and Needs Assessment (RDNA4) : February 2022 - December 2024 - World Bank; Government of Ukraine; European Union; United Nations (World Bank Group, 2025)
Ukraine - Fourth Rapid Damage and Needs Assessment (RDNA4) : February 2022 - December 2024 (English)
KerkoCite.ItemAlsoKnownAs: 2339240:IJ96WCZ9 2405685:KC4WLEL9